Canadian Court Rules Physical Education Teacher Negligent: Editor: Thomas H. Sawyer. Issue 4 (4th May 2019) - Sawyer, Tonya L.
Abstract : The court found that the physical education teacher fell below the standard of care by allowing a seventh-grade student to play field hockey in physical education class although the student lacked both the experience and the proper instruction to play this particular sport.